Sex-specific ultrasound imaging biomarkers of neurodegeneration in a mouse model - Mark B. Russell; Drew P. Locke; Haley M. Adams; Alexander R. Pelley; Rojan Saghian; Rojan Saghian; Alexandre S. Maekawa; Darcie Stapleton; Grace V. Mercer; John G. Sled; John G. Sled; John G. Sled; et al. (Frontiers in Aging Neuroscience)
IntroductionEarly detection of neurodegeneration is essential for optimizing interventions. The highly reproducible progression of neurodegeneration in the decrepit (dcr) mouse allows investigation of early biomarkers and mechanisms of brain injury.MethodsUsing high-frequency ultrasound, the common carotid arteries of female and male dcr and control mice were imaged longitudinally at time points bracketing the disease progression (50, 75, and 125 days of age) (n = 6 mice/group/sex).ResultsOver the disease time course, the female dcr mice demonstrated increased carotid artery blood flow and pulse wave velocity while the male dcr mice had a decrease in heart rate and no change in carotid artery ultrasound parameters. Early imaging biomarkers were sex-specific, with decreased carotid artery blood flow in female dcr mice and increased carotid artery diameter and decreased pulse wave velocity in males.DiscussionCarotid artery and wave reflection ultrasound is a promising screening tool for early detection of neurodegeneration.